Low frequency temporal modulation of light promotes a myopic shift in refractive compensation to all spectacle lenses. - Crewther, S; Barutchu, A; Murphy, M; Crewther, D (2006)
Emmetropization, the process by which ocular growth of young animals adapts to ensure focussed retinal images, can be disrupted by high frequency flicker, causing a hypermetropic shift. Emmetropization can also be disrupted differentially, in a sign dependent manner, by pharmacological alteration of the balance of activation of the ON and OFF retinal sub-systems in normal light or by rearing in an environment with a moving spatiotemporally varied diamond pattern (yielding local sawtooth illumination on the retina). Thus the aim of this experiment was to determine whether low frequency temporal modulation alone was sufficient to cause defocus sign-dependent interference with compensation. Chicks were reared for 6 or 7 days with monocular +/-10 D, 0 D, or No Lenses in a 12h light/dark cycle. Luminance of the environment was temporally modulated during the light cycle with a non-square wave profile pulse of 250 msec duration, with the illumination fluctuating between 1.5 and 180 lux at 1 Hz, 2 Hz, 4 Hz or with no flicker (0 Hz-180 lux). Final refractive state and ocular dimensions, measured using retinoscopy and A-scan ultrasonography, demonstrated that in the absence of temporal luminance modulation (0 Hz), chicks compensated to induced defocus in the expected sign-dependent manner. However, under 1, 2 and 4 Hz flickering light conditions, there was an overall myopic offset of approximately 6D across lens groups with refractive compensation to positive lenses more strongly inhibited. This myopic offset was reflected by increases in the depth of both vitreous and anterior chambers. However, luminance modulation had no effect on refraction or ocular parameters in the No Lens conditions. This is a hitherto unreported strong interaction between lens wear and low frequency temporally modulated light, with the refractive compensation mechanism being overridden by a generalized myopic shift.